Error-correction versus Differencing in Macroeconomic Forecasting - O. Eitrheim; T.A. Husebo; R. Nymoen (University of Oslo, Department of Economics, 1998)
Recent work by Clements and Hendry have shown why forecasting systems that are in terms of differences, dVARs, can be more accurate than econometric models that include levels variables, ECMs. For example, dVAR forecasts are insulated from parameter non-constancies in the long run mean of the cointegration relationships. In this paper, the practical relevance of these issues are investigated for RIMINI, the quarterly model of the Central Bank of Norway, which we take as an example of an ECM forecasting model.
Keywords: C53; E27; E47; 330; forecasts; macroeconomics